"Experts by Experience": The Involvement of Service Users and Families in Designing and Implementing Innovations in Family Justice. (18th July 2019) - Misca, Gabriela; Walker, Janet; Kaplan, Carole
Abstract : Drawing on international research, policy, and practice, this article explores what is meant by service user involvement, how it has developed, and how it has been implemented across different areas of practice. Using examples from across the health and social care fields, it reflects on how the learning from other areas of practice in which service user involvement has been successful may be applied to the family justice field. The arguments presented highlight the value of taking a bottom‐up approach in designing and implementing innovations in family justice, which would embrace the views of family members, including children, as 'service users.' It is important, however, to balance both the challenges and the opportunities offered by involving those who are 'experts by experience' in the family justice processes, in order to lead to improved services and experiences. Key Points for the Family Court Community: Family justice systems have traditionally been devised and operated by the professionals that deliver the services. However, in recent years, there has been increasing recognition of the value of involving "service users" and families in designing and implementing innovations in family justice, resulting in a smarter, less bureaucratic, and more accessible family law system. Successful examples from other professional areas (such as health and social care) highlight the value of taking a bottom‐up approach in designing and implementing innovations in family justice, which would embrace the views of family members, including children, as 'service users.' However, in order to lead to improved services and experiences, it is essential to balance both the challenges and the opportunities offered by involving those who are 'experts by experience' in the design and implementation of family justice processes.